Ancient Angkor - Freeman, Michael 1945-; Jacques, Claude (Bangkok River Books, 2003)
Guide to art and architecture of Angkor, extinct city, Cambodia.
UPSA-1817g donated by Eliza Romualdez-Valtos
Keywords: Architecture, Khmer -- Cambodia -- Angkor (Extinct city); Temples -- Cambodia -- Angkor (Extinct city); Angkor (Extinct city).; Angkor (Extinct city) -- Pictorial works; Angkor (Extinct city) -- Buildings, structures, etc; Cambodia -- Antiquities